Technical and economic analysis of full and empty crossing methods in the sequence of station and tunnel construction in Tehran metro line seven - Seyed Amirhossein Ghoreishian; Amin Jafarniya; Mohammad Fayyaz; Saeed Mohammad (مهندسی و مدیریت ساخت, 2020)
Due to the expansion of urban spaces and as well as the lack of necessary spaces for intra-city transportation, the need for subway construction in urban areas is more acute than ever. In order to build a subway,it is necessary to build underground structures such as tunnels and several stations.Today, one of the most important construction issues in metro projects is deciding on the sequence of tunnel or station construction. Obviously, proper allocation of resources to different departments requires careful technical and economic consideration of different options and special attention to aspects related to work planning. In this research, two methods of tunnel or station execution sequence in two general cases of full and empty passage have been investigated.Furthermore, considering that each of the above methods requires the adoption of measures to prevent possible problems and delays, these arrangements have been stated in each case.Finally, the economic comparison of the sequence of tunnel construction and the station in the seven metro lines of Tehran has been studied.Studies show that the construction of the tunnel before the construction of the station is more economical than the construction of the station before the construction of the tunnel. And this can save a lot of money for a metropolis like Tehran, which needs to build a large number of subway lines and stations. Also, familiarity with the costs, obstacles and problems of each of the above methods can be useful in deciding on the appropriate method and contract to start a rail project.